Keanekaragaman Serangga Permukaan Air di Sungai Batu Gong Desa Tataba Kecamatan Buko Kabupaten Banggai Kepulauan - Firga Nabila Lige; Sulasmi Anggo; Wahyudin Abdul Karim; Nurtini Samak (Jurnal Biologi Babasal, 2022)
Insects can be found in almost all areas above the earth’s surface, on land, sea and air. Insect life has existed since 400  milion years ago, ranging from 2-3 milion insect species that have been identified. Insects are one of the groups of animals that have high level of diversit. This study aims to determine the diversity of surface water insects in the Batu gong river, Tataba Village, Buko District, Banggai Islands Regency. The type of research used was descriptive quantitative at Batu Gong River, Tataba Village, Buko District, Banggai Islands Regency. The sampling technique was carried out using the roaming method. The data were analyzed using the Shannon Winner Diversity Index. The results of this study indicate that the diversity of surface water insects in the Batu Gong River, Tababa Village, Buko District, Banggai Islands Regency was in the medium category whit a value of 1.71 At each station starting from station 1, the diversity index was found at a value of 1.72 in the medium category, while at station 2, the diversity index was at a value of 1.65 whit as medium category, and station 3, the diversity index was at a value of 1.62 with a lower category.Keywords:  Water Insects, Batu Gong River